A multidimensional view? Evaluating the different and combined contributions of diaries and interviews in an exploration of asexual identities and intimacies. (October 2017) - McDonnell, Liz; Scott, Susie; Dawson, Matt
This article evaluates the relative contributions of diaries and interviews in multiple methods qualitative research exploring asexual identities and intimacies. Differentiated by three core differences: reflective time-frame (the day just had/lifetime), context (alone/with researcher) and mode (written/verbal), these methods had the potential to generate a multidimensional view of our topics. Using five cases in which data from both interviews and diaries were collected, this article explores how the intermeshed issues of identity and intimacy were constructed in each method, as well as reflecting on what was gained by their combination. Our analysis leads us to conclude that multiple methods do not always produce a fuller or a more rounded picture of individual participants' lives. Nevertheless, the decision to collect data using different strategies did increase our chances of finding a method that suited individual participants, whether in style or focus.